Burn after reading: Operation Focus and the fictional Nemzeti Ellenzéki Mozgalom in the lead-up to the 1956 Hungarian Uprising. Issue 2 (3rd April 2023) - Roth, Sarah
ABSTRACT: From 1954 to 1956, the Free Europe Press, sister organisation to Radio Free Europe, engaged in a covert propaganda campaign known as Operation Focus. Writing under the alias of the fictional Hungarian partisan group Nemzeti Ellenzéki Mozgalom, the campaign encouraged widespread passive resistance against the communist regime through a coordinated print and radio campaign facilitated via specially-designed weather balloons and RFE broadcasts, respectively. Under pressure from the Hungarian and US governments, the campaign came to end just days before the outbreak of the 1956 Hungarian Rising.